2016
DOI: 10.1890/15-0050
|View full text |Cite
|
Sign up to set email alerts
|

Cascade of ecological consequences for West Nile virus transmission when aquatic macrophytes invade stormwater habitats

Abstract: Artificial aquatic habitats are ubiquitous in anthropogenic landscapes and highly susceptible to colonization by invasive plant species. Recent research into the ecology of infectious diseases indicates that the establishment of invasive plant species can trigger ecological cascades which alter the transmission dynamics of vector-borne pathogens that imperil human health. Here, we examined whether the presence or management of two invasive, emergent plants, cattails (Typha spp.) and phragmites (Phragmites aust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 68 publications
1
18
0
Order By: Relevance
“…Larger adults that emerged from microcosms with S. arundinaceus were likely exposed to much greater microbial food, while the higher nutrient concentrations fouled the water, as indicated by a thick microbial film that coated the water surface ( personal observation ), presumably causing lethally toxic conditions for a proportion of the larvae. These results are consistent with previous laboratory and field studies of the effects of detritus species and resultant food resources on mosquito performance (e.g., [10,11,15,73]), including those that have demonstrated increased survival and abundances from fresh compared to senescent detritus [14,36]. S. arundinaceus also leached higher tannin-lignin concentrations than other detritus species, reaching a maximum of 40 mg/L over the study duration.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Larger adults that emerged from microcosms with S. arundinaceus were likely exposed to much greater microbial food, while the higher nutrient concentrations fouled the water, as indicated by a thick microbial film that coated the water surface ( personal observation ), presumably causing lethally toxic conditions for a proportion of the larvae. These results are consistent with previous laboratory and field studies of the effects of detritus species and resultant food resources on mosquito performance (e.g., [10,11,15,73]), including those that have demonstrated increased survival and abundances from fresh compared to senescent detritus [14,36]. S. arundinaceus also leached higher tannin-lignin concentrations than other detritus species, reaching a maximum of 40 mg/L over the study duration.…”
Section: Discussionsupporting
confidence: 90%
“…Fewer studies have examined the effects of detritus type on larval mosquito performance in ground pool habitats, but at least one study has shown that the mowing of invasive Phragmites australis and Typha spp. around the perimeters of stormwater detention ditches dramatically increased abundances of larval mosquitoes in the ditches and adults infected with West Nile virus (WNV) in adjacent resident areas [36].…”
Section: Introductionmentioning
confidence: 99%
“…IAPS in the aquatic environments also have human health implications (Plaza et al, 2018;Stone et al, 2018). The prominent aquatic IAPS like Phragmites australis and Typha assist in the colonization and multiplication of vector-borne pathogens, particularly West Nile virus (MacKay et al, 2016) (Table 2). Eichhornia crassipes (water hyacinth) is also a high risk IAPS, helping in the spread of schistosomiasis (Mazza et al, 2014;Gezie et al, 2018;Stone et al, 2018).…”
Section: Impacts Of the Iaps On Human Healthmentioning
confidence: 99%
“…Plant communities in urban ponds include a large proportion of non-native species, including invasive species (Magee et al 1999, Ehrenfeld 2008, and this has consequences for native biodiversity. These non-native plant species can trigger a cascade of altered species interactions (Mackay et al 2016). Such ecosystem changes can even lead to the changes of the transmission dynamics of vector-borne pathogens that imperil human health, such as West Nile virus in mosquitoes (Mackay et al 2016).…”
Section: Non-native Invasive Speciesmentioning
confidence: 99%
“…These non-native plant species can trigger a cascade of altered species interactions (Mackay et al 2016). Such ecosystem changes can even lead to the changes of the transmission dynamics of vector-borne pathogens that imperil human health, such as West Nile virus in mosquitoes (Mackay et al 2016). Non-native vegetation can also negatively impact vertebrate presence.…”
Section: Non-native Invasive Speciesmentioning
confidence: 99%